Emotionally clocked out: cell-type specific regulation of mood and anxiety by the circadian clock system in the brain - Francis, T. Chase; Porcu, Alessandra (Frontiers in Molecular Neuroscience, 2023)
Circadian rhythms are self-sustained oscillations of biological systems that allow an organism to anticipate periodic changes in the environment and optimally align feeding, sleep, wakefulness, and the physiological and biochemical processes that support them within the 24 h cycle. These rhythms are generated at a cellular level by a set of genes, known as clock genes, which code for proteins that inhibit their own transcription in a negative feedback loop and can be perturbed by stress, a risk factor for the development of mood and anxiety disorders. A role for circadian clocks in mood and anxiety has been suggested for decades on the basis of clinical observations, and the dysregulation of circadian rhythms is a prominent clinical feature of stress-related disorders. Despite our understanding of central clock structure and function, the effect of circadian dysregulation in different neuronal subtypes in the suprachiasmatic nucleus (SCN), the master pacemaker region, as well as other brain systems regulating mood, including mesolimbic and limbic circuits, is just beginning to be elucidated. In the brain, circadian clocks regulate neuronal physiological functions, including neuronal activity, synaptic plasticity, protein expression, and neurotransmitter release which in turn affect mood-related behaviors via cell-type specific mechanisms. Both animal and human studies have revealed an association between circadian misalignment and mood disorders and suggest that internal temporal desynchrony might be part of the etiology of psychiatric disorders. To date, little work has been conducted associating mood-related phenotypes to cell-specific effects of the circadian clock disruptions. In this review, we discuss existing literature on how clock-driven changes in specific neuronal cell types might disrupt phase relationships among cellular communication, leading to neuronal circuit dysfunction and changes in mood-related behavior. In addition, we examine cell-type specific circuitry underlying mood dysfunction and discuss how this circuitry could affect circadian clock. We provide a focus for future research in this area and a perspective on chronotherapies for mood and anxiety disorders.